Donaciano Vigil : The Life of a Nuevomexicano Soldier, Statesman, and Territorial Governor - Vigil, Maurilio E., 1941-; Boudreau, Helene (Book collections on Project MUSE., 2022)
In this gripping biography of a remarkable man, Maurilio E. Vigil and Helene Boudreau fill the gap within the scholarship on Hispanics in nineteenth-century New Mexico.